CREPT/RPRD1B associates with Aurora B to regulate Cyclin B1 expression for accelerating the G2/M transition in gastric cancer. Issue 12 (December 2018) - Ding, Lidan; Yang, Liu; He, Yuqi; Zhu, Bingtao; Ren, Fangli; Fan, Xuanzi; Wang, Yinyin; Li, Mengdi; Li, Jun; Kuang, Yanshen; Liu, Sihan; Zhai, Wanli; et al.
Abstract Gastric cancer, like most of other cancers, has an uncontrolled cell cycle regulated by cyclins and cyclin-dependent kinases (CDKs). In this study, we reported that gastric cancer cells showed an accelerated G2/M transition promoted by CREPT/RPRD1B and Aurora kinase B (Aurora B). We found that CREPT/RPRD1B and Aurora B were coordinately expressed during the cell cycle in gastric cancer cells. Deletion of CREPT/RPRD1B disturbed the cell progression and extended the length of cell cycle, leading to a significant accumulation of mitotic cells. Mechanistically, we revealed that CREPT/RPRD1B interacted with Aurora B to regulate the expression of Cyclin B1 in gastric cancer cells. Interestingly, Aurora B phosphorylates S145 in a well-conserved motif of CREPT/RPRD1B. We proposed that phosphorylation of CREPT/RPRD1B by Aurora B is required for promoting the transcription of Cyclin B1, which is critical for the regulation of gastric tumorigenesis. Our study provides a mechanism by which gastric tumor cells maintain their high proliferation rate via coordination of Aurora B and CREPT/RPRD1B on the expression of Cyclin B1. Targeting the interaction of Aurora B and CREPT/RPRD1B might be a strategy for anti-gastric cancer therapy in the future.